Pengelolaan Penggajian Guru di SMAN 12 Surabaya - Santoso, Nabila Dwi Wahyu; Maulana, Mokhamad Nizar; Bikhubbillah, Moh A'rif; Trihantoyo, Syunu; Nuphanudin, Nuphanudin (TSAQOFAH, 2024)
Good quality education can be seen from several factors, one of which is teacher motivation in carrying out teaching at school. With good motivation, a teacher can do his job well too. The way to increase a teacher's motivation is good payroll management. Effective payroll management is critical to maintaining teacher satisfaction and motivation. This article aims to find out how SMAN12 Surabaya manages salaries for civil servant and non civil servant teachers, where these salaries can influence teacher motivation in carrying out their duties and responsibilities. Using qualitative methods and collecting data using interview, observation and documentation techniques. The research results show that at SMAN 12 Surabaya there are differences in salary management for PNS and non-PNS teaching staff, but salary management at SMAN 12 Surabaya can also influence teacher motivation to carry out their duties and responsibilities as a teacher to improve the quality of education.